2018
DOI: 10.1111/jipb.12637
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose synthase ‘class specific regions’ are intrinsically disordered and functionally undifferentiated

Abstract: Cellulose synthases (CESAs) are glycosyltransferases that catalyze formation of cellulose microfibrils in plant cell walls. Seed plant CESA isoforms cluster in six phylogenetic clades, whose non-interchangeable members play distinct roles within cellulose synthesis complexes (CSCs). A 'class specific region' (CSR), with higher sequence similarity within versus between functional CESA classes, has been suggested to contribute to specific activities or interactions of different isoforms. We investigated CESA iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 79 publications
4
19
0
Order By: Relevance
“…Emerging results have indicated that the locations of the interfaces that determine class‐specific interaction vary among CESA classes in Arabidopsis (Carroll and Specht, ; Kumar et al ., ; Hill et al ., ) and P. patens (Scavuzzo‐Duggan et al ., ), as expected if hetero‐oligomeric complexes evolved convergently. With only two functionally distinct CESA classes and more functional redundancy (Li, ; Norris et al ., ; Scavuzzo‐Duggan et al ., ), it appears that CESA functional differentiation is less well developed in P. patens compared with seed plants. This finding is likely to reflect the relatively recent occurrence of genome duplications in P. patens (27–48 mya) (Lang et al ., ), whereas the duplications that generated the six seed plant CESA clades occurred before the divergence of gymnosperms and angiosperms, over 200 mya (Zeng et al ., ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Emerging results have indicated that the locations of the interfaces that determine class‐specific interaction vary among CESA classes in Arabidopsis (Carroll and Specht, ; Kumar et al ., ; Hill et al ., ) and P. patens (Scavuzzo‐Duggan et al ., ), as expected if hetero‐oligomeric complexes evolved convergently. With only two functionally distinct CESA classes and more functional redundancy (Li, ; Norris et al ., ; Scavuzzo‐Duggan et al ., ), it appears that CESA functional differentiation is less well developed in P. patens compared with seed plants. This finding is likely to reflect the relatively recent occurrence of genome duplications in P. patens (27–48 mya) (Lang et al ., ), whereas the duplications that generated the six seed plant CESA clades occurred before the divergence of gymnosperms and angiosperms, over 200 mya (Zeng et al ., ).…”
Section: Discussionsupporting
confidence: 75%
“…Our previous results suggested that convergent CESA sub‐functionalization in the moss and seed plant lineages resulted from similar selective pressure favoring regulatory uncoupling of the CESAs that synthesize primary and secondary cell walls (Norris et al ., ). Taken together, evidence that the secondary PpCESAs form hetero‐oligomeric CSCs (Figures ), that class A and class B secondary PpCESAs are not interchangeable (Norris et al ., ; Scavuzzo‐Duggan et al ., ), and that PpCESA3 / PpCESA8 and PpCESA6 / PpCESA7 constitute redundant pairs (Wise et al ., ; Norris et al ., ) is consistent with PpCESA neo‐functionalization such that members of class A (PpCESA3 or PpCESA8) and class B (PpCESA6 or PpCESA7) occupy distinct positions within the CSCs (Figure ). If PpCESA7 is unique in its ability to self‐interact, as indicated by results of MbYTH and BiFC results (Figures and ), then the class B PpCESA may occupy two positions within each lobe (gray subunits in Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations